Utilizing National Cropping Calendar Atlas in Copping with Variability and Climate Change - ELEONORA RUNTUNUWU; H. SYAHBUDDIN (Jurnal Sumberdaya Lahan, 2011)
Inappropriate cropping season and pattern resulted in the low production of seasonal food crops and the major cause of crop failure. A local wisdom called “Pranatamangsa” previously used to determine cropping time, now often miss due to climate anomaly. Crop growth is much affected by rainfall, solar radiation, and air temperature. The rainfall determines water availability and is essential requirement for crop growth. Planting time and cropping pattern until recently are adjusted to the climate variability and water availability to the crops. Therefore, the cropping calendar contained in this atlas is based on climate variability such as wet (El-Nino), normal, and dry (La-Nina) years. The atlas provides detailed description of planting time and crop rotation in each sub-district for each season in one year based on climate condition. The preparation of cropping calendar, both spatially and tabularly, provides information on cropping alternative for wet, normal or dry years. These alternatives were developed at 1:250 000 scale to be applied as reference in determining planting time and cropping pattern for each region and sub district. Hence, the risks of yield lost or crop failure can be avoided or minimized. Further, the policy and strategy of procurement and distribution of farm inputs particularly fertilizer and seed can be properly formulated. This cropping calendar was arranged through several steps: (1) climate data collection and farmer’s interview, (2) analysis of planting time and mapping, (3) field verification, and (4) refining the delineation of cropping pattern based on the sensitivity level. For a better planning of cropping time and pattern, this cropping calendar was arranged at the scale of 1:250.000 and attached with an information of cropping time and pattern at the sub-district level.